The Effectiveness of Contextual Approaches in Learning Moral Beliefs on the Learning Interests of Madrasah Ibtidaiyah Students - Qoyyimah, Dinul; K, Nurdin; Musa, Lisa Aditya Dwiwansyah; Nurwahidah, Nurwahidah (Educational Journal of Learning Technology, 2025)
This study aims to determine the effectiveness of applying a contextual approach in increasing students' interest in learning Moral Beliefs at MI Batulotong. The background of this research is based on the low interest in learning of students, which affects learning outcomes. The study uses a quantitative approach with a pre-experimental design and a pretest-posttest one-group model. Data were collected through questionnaires and analyzed using t-tests to see differences in learning interests before and after treatment. The study's results show that applying a contextual approach significantly increases students' interest in learning. The increase is evident in the higher average score of learning interest after treatment, as indicated by a t-test significance value of < 0.05. These findings demonstrate that real-life context-based learning can effectively motivate learners, increase active engagement, and foster a more meaningful learning environment.